2021
DOI: 10.1007/s10735-021-09970-4
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women with COVID-19: the placental involvement and consequences

Abstract: SARS-CoV-2, the leading cause of COVID-19 pandemic, was detected for the first time in Wuhan. In this study, we investigated the potential undesirable maternal and feto-neonatal consequences of COVID-19, and the related pathophysiological alterations in mother, neonate, and especially in the placenta as a vital organ, were reviewed. Also, the possibility of vertical transmission of virus and placental abnormalities were evaluated. The pregnant women were a vulnerable population for COVID-19, and several obstet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 101 publications
(69 reference statements)
2
22
0
9
Order By: Relevance
“…Majority of the pregnant women had mild symptoms of COVID-19 (73.5%) and only 26.5% had moderate to severe manifestation. Consistently, a previous study reported 86.0% mild cases and around 14.0% between severe and critical cases among pregnant women infected with COVID-19 15 . Additionally, similar proportions were observed among the general population 16 .…”
Section: Discussionsupporting
confidence: 88%
“…Majority of the pregnant women had mild symptoms of COVID-19 (73.5%) and only 26.5% had moderate to severe manifestation. Consistently, a previous study reported 86.0% mild cases and around 14.0% between severe and critical cases among pregnant women infected with COVID-19 15 . Additionally, similar proportions were observed among the general population 16 .…”
Section: Discussionsupporting
confidence: 88%
“…Adverse pregnancy outcomes, such as placental abruption, preterm delivery, and stillbirth, are linked to placental maternal vascular malperfusion (MVM) lesions, with a higher prevalence in infected pregnant women as compared to a control group. 40 MVM lesions may be associated with the duration, timing, and severity of the infection, which, in turn, can result in preterm deliveries. 20 There is a recognizable pattern of placental injury associated with abnormal uterine perfusion.…”
Section: Pathophysiology Of Placental Infection In Pregnancymentioning
confidence: 99%
“…The data on the consequences of SARS-CoV-2 infection during pregnancy on both maternal and fetal outcomes is limited. A key concern has been whether SARS-CoV-2 may infect or cross the placenta [ 44 ]. A recent review including 1457 pregnancies concluded that the risk of premature birth, maternal death, fetal death, fetal distress, and neonatal asphyxia were all increased in pregnancies affected by SARS-CoV-2 [ 45 ].…”
Section: Maternal To Fetal Transmission Of Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%